The Phenomenon of Emmanuel Macron. Book review of ‘Qu’est-ce que le macronisme?’ edited by E. Fottorino - P. G. Loginova (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The book under review is a collection of essays ‘Qu’est-ce que le macronisme?’ (‘What is Macronism’?), published by ‘Philippe Rey’ in 2018. The reviewer thoroughly considers the structure and the contents of the book. Each chapter represents an essay, an interview or an article by a prominent scholar, a politician or a journalist who present their views on the presidency of E. Macron and prospects for the development of France. The reviewer notes that the general tenor of the book is positive: all authors emphasize high intelligence and ambitions of the French leader, which facilitated greatly his career development from a little-known politician to the head of the state. The reviewer concludes that this popular science edition oﬀers a suﬃciently accurate political portrait of E. Macron, provides interesting biographical details and can be recommended for IR scholars, political scientists, journalists, and linguists since it is written in an impressive and elegant French language. The book under review can also prove useful in studying the role of an individual in history.